EFEKTIVITAS PELAYANAN PUBLIK PADA KANTOR SEKRETARIAT DAERAH KABUPATEN WAJO - Andi Aditya Putra; Andi Rusdi Untung; Iwan Mamminanga (BADAN PENERBIT STIEPARI PRESS, 2023)
Destination; to find out how the effectiveness of public services at the Regional Secretariat Office of Wajo Regency and to describe the obstacles faced by the effectiveness of public services at the Regional Secretariat Office of Wajo Regency, by using a type of descriptive qualitative research with data collection techniques through in-depth interviews, in-depth observation and data analysis interactively through the process of data reduction, data display, and drawing conclusions and verification, as well as in testing the validity of the data the author uses a data credibility test by extending participation observations, triangulation, discussions with colleagues. Transferability, dependability and confirmability tests.